Artemisia argyi-Mediated Synthesis of Monodisperse Silver Nanoparticles as Components of Bioactive Nanofibrous Dressings with Dual Antibacterial and Regenerative Functions - Jiale Wang; Jiawei Guan; Xingyu Ma; Dongyang Zhao; Yongqiang Han; Dongdong Guo; Jialin Bai; Zisheng Guo; Xiaojun Zhang (Journal of Functional Biomaterials, 2025)
The effective healing of chronic wounds requires balancing antimicrobial activity with tissue regeneration. In this study, we developed a novel, eco-friendly synthesis method using Artemisia argyi extract to produce silver nanoparticles (AgNPs), addressing toxicity concerns associated with conventional chemical synthesis methods. Through optimization of multiple synthesis parameters, monodisperse spherical AgNPs with an average diameter of 6.76 ± 0.27 nm were successfully obtained. Plant-derived compounds from Artemisia argyi extract acted as efficient mediators for both reduction and stabilization, yielding nanoparticles with high crystallinity. The synthesized AgNPs exhibited potent antibacterial activity against both Gram-negative and Gram-positive bacteria, with minimum inhibitory concentrations of 8 μg/mL against Escherichia coli and 32 μg/mL against Staphylococcus aureus, while maintaining high biocompatibility with L929 fibroblasts at concentrations ≤ 8 μg/mL. When integrated into polylactic acid/collagen type I (PLA/Col1) nanofibrous matrices, the optimized 0.03% AgNPs/PLA/Col1 dressing significantly accelerated wound healing in a diabetic rat model, achieving 94.62 ± 2.64% wound closure by day 14 compared to 65.81 ± 1.80% observed in untreated controls. Histological analyses revealed a dual-functional mechanism wherein controlled silver ion release provided sustained antibacterial protection, while concurrently promoting tissue regeneration characterized by enhanced collagen deposition, reduced inflammation, and increased neovascularization. This innovative approach effectively addresses critical challenges in diabetic wound care by providing simultaneous antimicrobial and regenerative functions within a single biomaterial platform.